Oxidative DNA damage preventive activity and antioxidant potential of plants used in Unani system of medicine - Chattopadhyay Sharmila; Banerjee Anindita; Bhattacharyya Dipto; Kalim Mehar (BMC, 2010)
Abstract Background There is increasing recognition that many of today's diseases are due to the "oxidative stress" that results from an imbalance between the formation and neutralization of reactive molecules such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), which can be removed with antioxidants. The main objective of the present study was to evaluate the antioxidant activity of plants routinely used in the Unani system of medicine. Several plants were screened for radical scavenging activity, and the ten that showed promising results were selected for further evaluation. Methods Methanol (50%) extracts were prepared from ten Unani plants, namely Cleome icosandra, Rosa damascena, Cyperus scariosus, Gardenia gummifera, Abies pindrow, Valeriana wallichii, Holarrhena antidysenterica, Anacyclus pyrethrum, Asphodelus tenuifolius and Cyperus scariosus, and were used to determine their total phenolic, flavonoid and ascorbic acid contents, in vitro scavenging of DPPH·, ABTS·+, NO, ·OH, O2.- and ONOO-, and capacity to prevent oxidative DNA damage. Cytotoxic activity was also determined against the U937 cell line. Results IC50 values for scavenging DPPH·, ABTS·+, NO, ·OH, O2.- and ONOO- were in the ranges 0.007 ± 0.0001 - 2.006 ± 0.002 mg/ml, 2.54 ± 0.04 - 156.94 ± 5.28 μg/ml, 152.23 ± 3.51 - 286.59 ± 3.89 μg/ml, 18.23 ± 0.03 - 50.13 ± 0.04 μg/ml, 28.85 ± 0.23 - 537.87 ± 93 μg/ml and 0.532 ± 0.015 - 3.39 ± 0.032 mg/ml, respectively. The total phenolic, flavonoid and ascorbic acid contents were in the ranges 62.89 ± 0.43 - 166.13 ± 0.56 mg gallic acid equivalent (GAE)/g extract, 38.89 ± 0.52 - 172.23 ± 0.08 mg quercetin equivalent (QEE)/g extract and 0.14 ± 0.09 - 0.98 ± 0.21 mg AA/g extract. The activities of the different plant extracts against oxidative DNA damage were in the range 0.13-1.60 μg/ml. Of the ten selected plant extracts studied here, seven - C. icosandra, R. damascena, C. scariosus, G. gummifera, A. pindrow, V. wallichii and H. antidysenterica - showed moderate antioxidant activity. Finally, potentially significant oxidative DNA damage preventive activity and antioxidant activity were noted in three plant extracts: C. icosandra, R. damascena and C. scariosus. These three plant extracts showed no cytotoxic activity against U937 cells. Conclusions The 50% methanolic extracts obtained from different plant parts contained significant amounts of polyphenols with superior antioxidant activity as evidenced by the scavenging of DPPH·, ABTS·+, NO, ·OH, O2.- and ONOO-. C. icosandra, R. damascena and C. scariosus showed significant potential for preventing oxidative DNA damage and radical scavenging activity, and the G. gummifera, A. pindrow, V. wallichii, H. antidysenterica, A. pyrethrum, A. tenuifolius and O. mascula extracts showed moderate activity. The extracts of C. icosandra, R. damascena and C. scariosus showed no cytotoxicity against U937 cells. In conclusion, these routinely used Unani plants, especially C. icosandra, R. damascena and C. scariosus, which are reported to have significant activity against several human ailments, could be exploited as potential sources of natural antioxidants for plant-based pharmaceutical industries.